Monitoring Visual Cortical Activities During Progressive Retinal Degeneration Using Functional Bioluminescence Imaging - Narcisse, Darryl; Mustafi, Sourajit M.; Carlson, Michael; Kim, Sanghoon; Batabyal, Subrata; Wright, Weldon; Mohanty, Samarendra K. (Frontiers in Neuroscience, 2021)
Mouse models of inherited retinal degenerative diseases such as retinitis pigmentosa are characterized by degeneration of photoreceptors, which hinders the generation of signal to be transmitted to the visual cortex. By monitoring Ca2+-bioluminescence neural activity, we quantified changes in visual cortical activities in response to visual stimuli in RD10 mice during progression of retinal degeneration, which correlated with progressive deteriorations of electro-retinography signal from the eyes. The number of active neurons in the visual cortex, the intensity of Ca2+-bioluminescence response, and neural activation parameter showed progressive deterioration during aging. Further, we correlated the thinning of retina as measured by Optical Coherence Tomography with the decrease in visual cortical activities as retinal degeneration progressed. The present study establishes Ca2+-bioluminescence monitoring as a longitudinal imaging modality to characterize activities in visual cortex of retinal degenerative disease models and therapeutic interventions.